ALZHEIMER'S IN THE QURAN - Nina Aminah (Ide Insan Kreatif, 2025)
Alzheimer's is the most common cause of dementia, a general term for memory loss and other cognitive impairments serious enough to interfere with daily life. Alzheimer's disease accounts for 60-80% of dementia cases. The most obvious symptom of Alzheimer's is memory loss. In Indonesia, the prevalence of dementia and Alzheimer's disease is around 27.9%. More than 4.2 million people suffer from dementia. Alzheimer's disease and dementia can affect anyone, but they are most common in older adults aged 50 and above. Seniors over the age of 65 have a higher risk of developing Alzheimer's disease. Risk factors associated with Alzheimer's and dementia include age, gender, nutritional status, physical activity, education level, and medical history. This study aims to provide information about Alzheimer's and dementia according to the Quran, provide information about the prevention of Alzheimer's and dementia so that they do not occur at a younger age, and identify the problems of Alzheimer's and dementia that often occur in the elderly. This study uses a qualitative approach with library research or literature study, which involves collecting data and processing it by reading and noting points considered important in this study. The researcher organized, grouped, allocated, and used various literature in this study. Through this literature review, a deeper understanding of Alzheimer's in the Quran can also be obtained. The results of this study show that the Quran has many virtues, is a cure that can heal, and that people who always make it a habit to read the verses of the Quran will always have peace of mind, thus staying away from depression or dementia, and will also receive perfect rewards